A mixed methods analysis of housing and neighbourhood impacts on community integration among vulnerably housed and homeless individuals. Issue 4 (31st January 2017) - Ecker, John; Aubry, Tim
Abstract: The current longitudinal study used mixed methods to examine the relationship of housing and neighborhood characteristics and community integration among a population of homeless and vulnerably housed individuals. Participants were recruited at homeless shelters, meal programs, and rooming houses in Ottawa, Canada, and participated in 3 in‐person interviews, each approximately 1 year apart. Participants were placed into either a "high" or a "low" integration group based on their community integration scores at Follow‐up 1 and Follow‐up 2. There were 14 high and 32 low integration participants at Follow‐up 1, and 17 high and 35 low participants at Follow‐up 2. A general inductive approach to analyzing qualitative data was used to code the data. The most salient themes that affected community integration involved substance use in one's housing and neighborhood, neighborhood safety and location, and housing quality. Implications for service provision and policy advancements to better address community integration are discussed.